Book Review: A.OMISSI, Emperors and Usurpers in the Later Roman Empire: Civil War Panegyric, and the Construction of Legitimacy, Oxford 2018 - STEWART, Michael Edward (Byzantina Symmeikta, 2020)
Book Review: A.OMISSI, Emperors and Usurpers in the Later Roman Empire: Civil War Panegyric, and the Construction of Legitimacy, Oxford 2018